Diagnostic performances of D-dimer, prothrombin time, and red blood cell distribution width for coronary artery lesion in children with acute stage Kawasaki disease - Yin, Qi-Gai; Zhou, Jing; Zhou, Qin; Shen, Lu; Zhang, Mei-Yu; Wu, Yan-Hui (Frontiers in Pediatrics, 2023)
Aim: To evaluate the performances of D-dimer, prothrombin time (PT), and red blood cell distribution width (RDW) for the diagnosis of coronary artery lesion (CAL) in acute stage Kawasaki disease (KD). Methods: Between January 2018 and January 2021, a total of 102 children with acute stage KD were included in this retrospective study. Among them, 36 KD children with CAL were divided into the CAL group, and 66 KD children without CAL were divided into the NCAL group. Independent predictors of CAL in acute stage KD were identified by using univariate and multivariate logistic regression analysis. Spearman correlations were used to evaluate the association between CAL in acute stage KD and different indicators. The diagnostic performance of different indicators for CAL in acute stage KD was analyzed by the receiver operating characteristic (ROC) curve. Results: Compared with the NCAL group, children in the CAL group had significantly higher white blood cell count, lymphocyte count, platelet count, D-dimer, and RDW levels, but lower PT levels (all p<0.05). Logistic regression analysis revealed that D-dimer (OR=1.0, 95% CI: 1.004-1.012, p<0.001), PT (OR=0.4, 95% CI: 0.2-0.8, p=0.01), and RDW (OR=7.0, 95% CI: 2.6-19.2, p<0.001) were independent predictors of CAL in children with acute stage KD. CAL showed a positive correlation with D-dimer (r=0.4, p<0.001) and RDW (r=0.5, p<0.001), and had a negative association with PT (r=-0.2, p<0.05). The ROC curve analysis showed that the combination of the three indicators had the highest diagnostic performance for CAL in acute stage KD with an area under the curve (AUC) of 0.922 (sensitivity, 86.1%; specificity, 89.4%), compared with D-dimer (AUC=0.736), PT (AUC=0.640), and RDW (AUC=0.819) alone. Conclusion: A combination of D-dimer, PT, and RDW may help predict CAL in children with acute stage KD.